LITERASI INFORMASI DALAM MEMAHAMI PEMIKIRAN NIDHAL GUESSOUM TENTANG INTEGRASI ANTARA SAINS DAN AGAMA ISLAM - Zulfikar Ghazali (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The purpose of this research is to find out how information literacy which is part of library science becomes an ability to understand the integration between science and Islam and its implementation in life. This type of research is qualitative with literature review data sources. Meanwhile, the literature review was conducted in four stages, consisting of: (a) focusing on the problem to be studied; (b) linking literature to problems in a balanced manner; (c) include a clear research statement based on the methodology in the literature; and (d) critically analyze and evaluate the reviewed literature based on the research discussion. For the research results, it can be seen that the Koran is a book of guidance not a book or a science encyclopedia, in other words all scientific phenomena that exist in the Koran are proof of the truth of the Koran, and it is clear al-Qur'an is truly the word that came down from Allah SWT. and given to Rasullullah Saw. to be conveyed and become a guide for humans who are on this earth. Al-Qur'an is a guide if someone always reads it, studies it, reflects on it and lives its meaning and implements or practices its contents which are implemented in everyday life. Studying science and religion are equally important, it's just that as Muslims we have priority in learning and mastering knowledge that is directly related to mahdhah worship. Nidhal Guessoum started his thoughts related to the idea of ​​integrating science and religion with the foundation of tauhid (the concept of God) and the Qur'an as his philosophical approach to science. Because there is no principle that is more central and central in Islam than the concept of God, and there is no more fundamental rule of law in the construction of Islam than the al-Qur'an. Nidhal also provides a solution for Muslims, especially in Islamic Science in order to develop in the future, such as the need to teach the philosophy of science, the need to revise and present the history of science properly, including the contribution of Islam and the birth of Modern Science, the need to have serious dialogue with theologians and Muslim scholars to ensure that science today contains many explanations on topics that they have monopolized for too long, the need to educate the public on issues that are somewhat close to the religious sphere, and finally the need to contract with non thinkers in the fields of science and religion